Effect of strain rate on flow stress and anisotropy of DP600, TRIP780, and AA5182-O sheet metal alloys. (February 2016) - Rahmaan, T.; Bardelcik, A.; Imbert, J.; Butcher, C.; Worswick, M.J.
Highlights: Strain rate effect on flow stress and anisotropic behavior of DP600, TRIP780 and AA5182-O sheet metal alloys are presented. DP600 and TRIP780 showed moderate rate sensitivity while AA5182-O showed relatively low or even negative rate sensitivity. Portevin–Le Châtelier (PLC) effect was observed in AA5182-O up to a strain rate of 1 s −1 . The Lankford coefficients were found to be relatively insensitive to strain rate for all three alloys. The Voce-Modified (VM) and Voce-Modified-Extrapolated (VME) models were utilized to capture the behavior of the materials. Abstract: This paper presents the results of an investigation into the rate sensitivity of DP600, TRIP780 and AA5182-O sheet metal alloys. The effect of strain rate on both the flow stress and anisotropy characteristics was also examined. Tensile experiments were performed at room temperature under conditions ranging from quasi-static to high strain rate loading on the three alloys in three orientations (0°, 45°, and 90°) with respect to the rolling direction. The longitudinal and width strains were measured with a biaxial extensometer for the quasi-static experiments and using Digital Image Correlation (DIC) methods for the elevated strain rate experiments. The DP600 and TRIP780 steels showed moderate rate sensitivity while AA5182-O showed relatively low or even negative rate sensitivity that was a function of strain rate. The Portevin–Le Châtelier (PLC) effect was observed in AA5182-O up to a strain rate of 1 s −1 and was considered to be the cause of the negative rate sensitivity. The hardening behavior of the TRIP780 at a strain rate of 1000 s −1 differed from that observed at lower strain rates. This difference is attributed to the effect of the adiabatic temperature rise on the transformation-induced plasticity effect (TRIP). The Lankford coefficients and the variation in flow stress with material orientation were relatively insensitive to strain rate for all three alloys. A number of constitutive fits were considered and validated successfully through finite element analysis simulations of the tensile experiments. The performance of the constitutive models was evaluated through comparison of the predicted and measured engineering stress–strain responses and the area reduction at the measured elongation at fracture.